Clinical characteristics and management of 106 patients with pyogenic liver abscess in a traditional Chinese hospital - Nie, ShiJiao; Lin, Da; Li, XiaoWen (Frontiers in Surgery, 2023)
This is a retrospective study of clinical data from 106 patients with pyogenic liver abscess (PLA) treated in a traditional Chinese hospital during the eight years preceding this publication. We aimed to provide evidence to improve the diagnosis accuracy and the treatment strategies for PLAs. We collected records of patients treated at the Guangxing Hospital, which is affiliated to the Zhejiang Traditional Chinese University in Hangzhou, and we collected their general background information, laboratory and imaging features, and clinical manifestations and outcomes to perform a retrospective analysis. Diabetes mellitus (45.3%, 48/106), biliary calculi (36.8%, 39/106), and history of abdominal surgery (15.1%, 16/106) were the three most common PLA risk factors present in our cohort. Fever and chills (95.3%, 101/106), right upper quadrant pain/epigastric discomfort (68.9%, 73/106), nausea and vomiting (38.8%, 41/106), and cough and sputum (14.2%, 15/106) were the most common clinical manifestations of PLA. Most patients had the abscesses in the right liver lobe, and the most commonly found bacteria were Klebsiella pneumoniae (54.8%, 42/76), Escherichia coli (35.1%, 27/76), and Streptococcus pneumoniae (3.9%, 3/76). Liver Doppler ultrasound is a conventional and effective method to identify liver abscesses. Most patients were treated using a percutaneous puncture under B-ultrasound guidance. Most patients (n = 104 or 98.1%) were cured, one patient (0.9%) died, and one was discharged with multiple abscesses post treatment.